Obstructive Sleep Apnea and Atherosclerosis - Zulkifli Amin; Hilman Z Amin; Lukman Z Amin (Interna Publishing, 2016)
Obstructive sleep apnea (OSA) is a sleep respiratory disorder characterized by recurrent episodes of complete or partial airway obstruction, resulting in apneas or hypopneas. OSA could contribute to atherosclerosis through direct and indirect mechanisms. Endothelial dysfunction, sympathetic stimulation, and proinflammatory cytokine modulation caused by OSA play significant role to an atherosclesrotic event. Other risk factors of atherosclerosis like hypertension and diabetes mellitus also associated with OSA. Animal and clinical studies recently showed promising data to prove association between OSA, atherosclerosis, and its risk factors. However, provided data has not showed consistent result. In the future, demand of further research both basic and clinical sciences need to be fulfilled.